Safety level of dynamic stability in waves of coastal sea-going ships in domestic waters - Peiqing YANG; Yaohua ZHOU (Zhongguo Jianchuan Yanjiu)
ObjectiveThe purpose of this study is to investigatethe safety risk of dynamic stability in waves of coastal sea-going ships in domestic waters by evaluating parametric roll, pure loss of stability and synchronous roll, based on the second generation intact stability assessment method for domestic ships. MethodThe Froude−Krylov assumption and free trim method are used to calculate the righting levers and stability characteristics in waves, simplified nonlinear motion equations and frequency-domain motion equation based on hydrodynamics are used to obtain the time/ frequency domain results of roll amplitude and acceleration of parametric and synchronous roll, and the stability characteristics are used to evaluate pure loss of stability. Finally the risk probabilities of three failure modes are obtained based on the probability of sea-states. ResultsThe study shows that the typical ship types may be vulnerable to pure loss of stability and synchronous roll, and assessment results of dynamic stability safety level in waves are generally consistent with the accident and investigation results. ConclusionThere is a risk of dynamic stability accidents in waves for typical Chinese coastal sea-going ship types. It is suggested that in the optimization of ship design, ship operation and sailing under adverse sea conditions, maritime supervision and accident investigation, special attention should be paid to the above safety level and accident risk assessment results.